Effect of Sr2+ doping on the linear and nonlinear optical properties of ZnO nanostructures. (January 2019) - Mani Rahulan, K.; Sahoo, Trilochan; Angeline Little Flower, N.; Phebe Kokila, I.; Vinitha, G.; Annie Sujatha, R.
Highlights: Sr 2+ doped ZnO nanostructures were synthesized by chemical precipitation method. Third-order NLO properties of the nanostructures have studied by a Z-scan technique at 532 nm. Experimental results from the samples show the existence of saturable absorption behavior. The better NLO response from the samples could be used for NLO device applications. Abstract: We present the structural and third order nonlinear optical properties of Sr 2+ -doped ZnO nanostructures synthesized by chemical precipitation technique. The prepared nanoparticles are systematically investigated by UV–vis absorption, X-ray diffraction (XRD), Photoluminescence spectroscopy and Field emission scanning electronic microscopy (FESEM), respectively. UV–vis absorption spectra show that the particles have a higher absorption in UV region and possess a large optical transparency in visible region. XRD patterns show that all the prepared nanoparticles are well crystallized with hexagonal wurtzite structure. The incorporation of Sr in ZnO was also confirmed by fluorescence quenching. FESEM images showed the formation of nanostructures with sheet-like structure. Third-order nonlinear optical properties of the nanostructures have been studied by Z-scan technique using diode pumped continuous wave (cw) laser system at a wavelength of 532 nm. Experimental results reveal that the materials exhibit saturable absorption (SA) and self-defocusing nature.